Permeation of lipidated protein in bilayer using unbiased simulations reveals signature motif for protein-membrane binding - Thukral, Lipi; Sengupta, Durba; Gokhale, Rajesh S. (Biophysical Journal, 2014)

Molecular mechanism underlying recruitment and insertion of lipid-anchored LC3 protein into membranes - Thukral, Lipi; Sengupta, Durba; Ramkumar, Amrita; Murthy, Divya; Agrawal, Nikhil; Gokhale, Rajesh S. (Biophysical Journal, 2015)
Lipid modification of cytoplasmic proteins initiates membrane engagement that triggers diverse cellular processes. Despite the abundance of lipidated proteins in the human proteome, the key determinants underlying membrane recognition and insertion are poorly understood. Here, we define the course of spontaneous membrane insertion of LC3 protein modified with phosphatidylethanolamine using multiple coarse-grain simulations. The partitioning of the lipid anchor chains proceeds through a concerted process, with its two acyl chains inserting one after the other. Concurrently, a conformational rearrangement involving the alpha-helix III of LC3, especially in the three basic residues Lys(65), Arg(68), and Arg(69), ensures stable insertion of the phosphatidylethanolamine anchor into membranes. Mutational studies validate the crucial role of these residues, and further live-cell imaging analysis shows a substantial reduction in the formation of autophagic vesicles for the mutant proteins. Our study captures the process of water-favored LC3 protein recruitment to the membrane and thus opens, to our knowledge, new avenues to explore the cellular dynamics underlying vesicular trafficking.

Mapping architectural and transcriptional alterations in non-lesional and lesional epidermis in vitiligo - Singh, Archana; Gotherwal, Vishvabandhu; Junni, Paivi; Vijayan, Vinaya; Tiwari, Manisha; Ganju, Parul; Kumar, Avinash; Sharma, Pankaj; Fatima, Tanveer; Gupta, Aayush; Holla, Ananthaprasad; Kar, Hemanta K.; et al. (Scientific Reports, 2017)
In vitiligo, chronic loss of melanocytes and consequent absence of melanin from the epidermis presents a challenge for long-term tissue maintenance. The stable vitiligo patches are known to attain an irreversible depigmented state. However, the molecular and cellular processes resulting in this remodeled tissue homeostasis is unclear. To investigate the complex interplay of inductive signals and cell intrinsic factors that support the new acquired state, we compared the matched lesional and non-lesional epidermis obtained from stable non-segmental vitiligo subjects. Hierarchical clustering of genome-wide expression of transcripts surprisingly segregated lesional and non-lesional samples in two distinct clades, despite the apparent heterogeneity in the lesions of different vitiligo subjects. Pathway enrichment showed the expected downregulation of melanogenic pathway and a significant downregulation of cornification and keratinocyte differentiation processes. These perturbations could indeed be recapitulated in the lesional epidermal tissue, including blunting of rete-ridges, thickening of stratum corneum and increase in the size of corneocytes. In addition, we identify marked increase in the putrescine levels due to the elevated expression of spermine/spermidine acetyl transferase. Our study provides insights into the intrinsic self-renewing ability of damaged lesional tissue to restore epidermal functionality in vitiligo.